Voluntary wheel running is capable of improving cognitive function only in the young but not the middle-aged male APPSwe/PS1De9 mice. (May 2021) - Wang, Guiping; Zhou, Huan-Huan; Luo, Lan; Qin, Li-Qiang; Yin, Jieyun; Yu, Zengli; Zhang, Lin; Wan, Zhongxiao
Abstract: To determine whether voluntary wheel running could improve cognitive function from both the young and middle-aged APP/PS1 mice and the underlying mechanisms involved in. Young (9-weeks old) and middle-aged (24-weeks old) APP/PS1 mice were randomly assigned into control and exercise groups, respectively. Mice from exercise group had free and unlimited access to the running wheel for a total of 16 weeks. Voluntary exercise only improved cognitive function from young but not the middle-aged APP/PS1 mice. This might be owing to that in young APP/PS1 mice voluntary exercise reduced tau phosphorylation via inhibiting p-GSK3β activity, as well as reduced neuro-inflammation and elevated key proteins involved in synaptic plasticity. Additionally, exercise also elevated circulating L-Valine, Glucosamine, Formylanthranilic acid, Myristic acid level and improved gut microbiota profiles (i.e. elevated Oscillibacter, EF097061_g, EU454870_g, EU504554_g, EU505046_g and EF096172_g and reduced Alistipes ). Improved circulating metabolites and intestinal microbiome might also contribute to improved learning and memory abilities post exercise. For the middle-aged APP/PS1 mice, exercise reduced ADAM10 and GFAP protein expression in hippocampus, with no notable alterations in circulating metabolites; additionally, mice from exercise group had markedly reduced abundance of the phyla Proteobacteria and Tenericutes, genera Bacteroides and Faecalibacterium, and elevated abundance of the genera Allobaculum . It is suggested that voluntary exercise should be initiated at an early adulthood period rather than at late stage in order to prevent cognitive decline or Alzheimer's disease. Graphical abstract: Voluntary running only improved cognitive function in the young but not the middle-aged APP/PS1 mice. Mechanistically, improved cognitive function post voluntary exercise might be owing to its beneficial effects on traditional AD pathology (i.e. voluntary exercise reduced tau phosphorylation via inhibiting p-GSK3β activity, as well as reduced neuro-inflammation and elevated key proteins involved in synaptic plasticity including BDNF and synaptophysin). Additionally, exercise also positively altered circulating metabolites, especially elevated circulating L-Valine, Glucosamine, Formylanthranilic acid, Myristic acid level. Also, exercise improved gut microbiota profiles (i.e. elevated Oscillibacter, EF097061_g, EU454870_g, EU504554_g, EU505046_g and EF096172_g and reduced Alistipes ). Improved circulating metabolites and intestinal microbiome might also contribute to improved learning and memory abilities post exercise, while precise mechanisms remain to be explored. Image 1 Highlights: Exercise only improved cognitive function in young APP/PS1 mice. Exercise reduced GSK3β activity and tau phosphorylation from young mice. Exercise improved neuro-inflammation and synpatic plasticity in young mice. Exercise improved circulating metabolites and intestinal microbiome in young mice.